Individual differences in timing of peak positive subjective responses to d-amphetamine: Relationship to pharmacokinetics and physiology. (April 2016) - Smith, Christopher T; Weafer, Jessica; Cowan, Ronald L; Kessler, Robert M; Palmer, Abraham A; de Wit, Harriet; Zald, David H
Rate of delivery of psychostimulants has been associated with their positive euphoric effects and potential addiction liability. However, information on individual differences in onset of d-amphetamine's effects remains scarce. We examined individual differences in the time to peak subjective and physiological effects and the pharmacokinetics/pharmacodynamics of oral d-amphetamine. We considered two independent studies that used different dosing regimens where subjects completed the drug effects questionnaire at multiple time points post d-amphetamine. Based on the observation of distinct individual differences in time course of drug effects questionnaire "feel", "high", and "like" ratings (DEQH+L+F ) in Study 1, subjects in both studies were categorized as early peak responders (peak within 60 minutes), late peak responders (peak > 60 minutes) or nonresponders; 20–25% of participants were categorized as early peak responders, 50–55% as late peak responders and 20–30% as nonresponders. Physiological (both studies) and plasma d-amphetamine (Study 1) were compared among these groups. Early peak responders exhibited an earlier rise in plasma d-amphetamine levels and more sustained elevation in heart rate compared to late peak responders. The present data illustrate the presence of significant individual differences in the temporal pattern of responses to oral d-amphetamine, which may contribute to heightened abuse potential.